ANALISIS KELAYAKAN PLTS ON-GRID MENGGUNAKAN SOFTWARE PVSYST 6.8.1 PADA PPSDM MIGAS - Adi Nugroho Pamungkas; Teguh Utomo; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
PPSDM Migas is a government-owned company engaged in the energy sector under the auspices of the auspices of the Ministry of Energy and Mineral Resource with a solar energy potential of 5,03 kWh/m2 /day obtained from the Meteonorm 7.1 software. PPSDM Migas has a total consumption of electrical energy in 2021 of 1,866 MWh. The construction of the On-Grid solar system at PPSDM Migas is expected to implement alternative energy resources and save electricity costs. The purpose of this study is to determine a feasibility analysis of solar power plants (PLTS) in technical and economic aspects using the PVsyst software simulation. The solar power plants system (PLTS) at PPSDM Migas has an installed capacity of 120 kWp which is divided into 8 point installation locations with a total of 420 units of solar panel with the Yingli Solar brand with a capacity of 280 Wp. There are 2 types of configuration systems based on their inverter capacity, which are the configuration of 10 kW inverter and 20 kW inverter. The PVsyst software simulation in 2021 produces 195,4 MWh per year of energy or can supply around 10,47% of the total energy consumption of PPSDM Migas. In 2021, this solar system is capable of producing 127,3 MWh of energy. Performance Ratio (PR) in one year is 84,4% from PVsyst, 85% from the theoretical calculation, and 58,9% from field results. The results of the economic feasibility analysis shot that Life Cycle Cost (LCC) is Rp. 2.021.116.083, and the value of the Cost of Energy (COE) is Rp. 963,59 /kWh.The results of the investment feasibility analysis show the value of Net Present Value (NPV) is Rp. 632.633.554, the value of the Profitibality Index (PI) is 1,36, and the Pay Back Period (PBP) or the year of return after the 14th year. Based on the results of the analysis in the technical aspects, it can conclude that the solar system at PPSDM Migas still needs performance improvement, while in the economic aspects, it is considered that the project is feasible to continue. Keyword: PLTS, PVsyst, PPSDM Migas